Potential therapeutic effects of the simultaneous targeting of the Nrf2 and NF-κB pathways in diabetic neuropathy() - Ganesh Yerra, Veera (Elsevier, 2013)
The Nuclear factor-2 erythroid related factor-2 (Nrf2) is a redox regulated transcription factor involved in the regulation of antioxidant defence systems. It drives the production of endogenous antioxidant defences and detoxifying enzymes. Nuclear factor-kappa light chain enhancer of B cells (NF-κB) is a transcription factor, involved in proinflammatory cytokine production, in addition to its immunological function. Both Nrf2 and NF-κB regulation are co-ordinated in order to maintain redox homeostasis in healthy cells. However, during pathological conditions this regulation is perturbed offering an opportunity for therapeutic intervention. Diabetic neuropathy is a condition, in which change in expression pattern of Nrf2 and NF-κB has been reported. This review aims to focus on the role of the Nrf2 and NF-κB in diabetic neuropathy and summarizes the therapeutic outcomes of various pharmacological modulators targeted at the Nrf2–NF-κB axis in diabetic neuropathy.